Prevalence of Different Types of Cancer Among Patient in Najaf Province/ Iraq - Abdul-Zahra, Noor I.; Taiban, Zahraa K. (Medical Science Journal for Advance Research, 2021)
This study was carried out in Middle Euphrates cancer center, laboratories department, Al-Najaf holy city - Iraq; Iraqi patients have been recorded during period January 2018 until December 2018. This study has demonstrated that four different types of the following cancers: Breast cancer, brain cancer, lung cancer and Bladder cancer were registered in this study. Comparison was occured among each type of cancer was regarded in sex, age and number. The highest levels of cancer among all the other types were breast and lung cancer , the majority results in cancer epidemiology for this study, which showed 22% and 8 % respectively. While in other types, the result has showed 6%, 4.7%,for Bladder cancer, and braian cancer, respectively